Cirurgia bariátrica: fragmentos da análise de uma espera - Sobral, Ana Luiza Oliveira (2013)
This study aims to analyze the obesity and its more extreme classification, morbid obesity, and also its forms of treatment, with emphasis on bariatric surgery, procedure that appears to solve the obesity problem, assuming often a magical character. Nowadays, the body plays a central role in life of the subject and it is the stage for changes that aim a perfect and healthy body. The medical discourse underlies this context when points out that the ideal body is healthy, providing higher quality of life and longevity to the subject. In this scenario, the obese is a deviant because it doesn´t have control over your body to achieve the healthy, it is far from the threshold of normality that medicine postulates. Treatments are attempting to program such body, through diet, exercise and, in more severe cases, drugs. Bariatric surgery is indicated when conventional treatment was unsuccessful and promises to reduce the IMC range for normal, improve comorbidities and consequently the quality of life of the subject. The main question of this work is what causes the subject to look for bariatric surgery. We got in the bariatric surgery program at the University Hospital of UFS to analyze the processes that occur in practice. Under the theoretical and methodological framework of psychoanalysis and focused on listening, we explored the field in the waiting room. The speeches of patients that were waiting consultation with the preparing team of the program, and others who already passed by, enriched this work. We concluded that the medical discourse can ignore the subject, their expectations and fears in this process, taking from him his involvement in the decision to perform surgery, and it ends up suggesting to the subject a form of treatment outwardly magical that cures obesity.